Latitudinal embryonic thermal tolerance and plasticity shape the vulnerability of oviparous species to climate change. Issue 3 (16th June 2021) - Sun, Bao‐jun; Ma, Liang; Wang, Yang; Mi, Chun‐rong; Buckley, Lauren B.; Levy, Ofir; Lu, Hong‐liang; Du, Wei‐Guo
Abstract: Heat tolerance at the immobile embryonic stage is expected to be critical in determining species vulnerability to climate change. However, how the mean and developmental plasticity of embryonic heat tolerance vary geographically, and how these geographic variations affect species' vulnerability under climate change remain unknown. We experimentally determined the mean and developmental plasticity of embryonic acute heat tolerance (EAHT, i.e., heat shock temperature at which embryonic heartbeats ceased) for three latitudinally distributed populations of an oviparous lacertid lizard. The experimental results suggested that the mean EAHT decreased with decreasing latitude and that the reaction norms of EAHT in relation to developmental temperatures showed "flat, " "bell‐shaped, " and "decreasing" patterns at high, medium, and low latitudes, respectively. Based on the means and plasticity of EAHT and weather data across China, we project that the heat stress frequency would increase from the present to the future and increase toward low latitudes. Furthermore, heat stress becomes more extensive with the incorporation of developmental plasticity. Incorporating the mean EAHT during the embryonic development season, heat stress frequency, and climate variables in a species distribution model projects that suitable habitats could move northward in response to ongoing climate change and shrink due to the loss of southern habitat. Moreover, even lizards within the areas that are predicted to remain highly suitable are expected to experience increases in heat stress over time, particularly at medium and low latitudes. Our study reveals geographic variation in the mean and developmental plasticity of EAHT and highlights its importance for predicting species vulnerability and range shifts in response to climate change.